Fatty acid composition of milk fat in grazing 'Serra da Estrela' ewes fed four levels of crushed corn - Marques M.R.; Belo C. (Production systems and product quality in sheep and goats, 2001)
One hundred and eight (108) grazing dairy 'Serra da Estrela' ewes were used in two lambing seasons (Autumn and Spring) to evaluate the effects of 4 levels of crushed corn (0, 300, 600 and 900 g) on milk composition and fatty acid (FA) composition of milk fat at 40, 60, 80 and 100 days of lactation. Milk fat and protein content did not change significantly with increasing levels of crushed corn. In Autumn, linolenic acid (C18:3), conjugated linoleic acid (CLA), branched-FA (BCFA) and odd-chain FA (OCFA) decreased significantly with supplementation. In Spring, medium chain FA (C12:0-C15:1) and saturated FA (SFA) significantly increased and C18:3 and OCFA decreased with increasing supplementation. Short chain FA (C4:0-C10:1), C12:0-C15:1 and C18:3 decreased significantly throughout the Spring lactation period, while long chain FA (LCFA), monounsaturated FA (MUFA), linoleic acid (C18:2), BCFA and OCFA increased.
Meeting of the Sub-Network on Production Systems of the FAO-CIHEAM Inter-Regional Cooperative Research and Development Network on Sheep and Goats, 1999/09/23-25, Molina de Segura-Murcia (Spain)